2022
DOI: 10.2174/2212796816666220330090107
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen’s Potential to Inhibit Planktonic and Biofilm Growth of Neisseria mucosa

Abstract: Background: Antibiotic resistance of various bacterial communities remains a global burden in healthcare industry. Biofilm formation is one of the resistance mechanisms acquired by bacterial communities in order to reverse the action of antibiotics. There is an urgent need for the discovery of novel antimicrobials and novel approaches to tackle this problem. However, it is very expensive and challenging to develop new antibiotics. Drug repurposing is an efficient strategy which reduces time and cost associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Additionally, ebselen inhibited swimming and swarming motility of S. marcescens, both regulated by the QS inducer acyl homoserine lactone (AHL). Molecular docking analysis validated the strong binding of ebselen to specifc QS proteins (1Joe and PigG) of S. marcescens via hydrogen bonds and aromatic interactions, indicating its potent antibioflm potential [93].…”
Section: Ebselen's Efect On Virulence Factors Of Gram-negativementioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, ebselen inhibited swimming and swarming motility of S. marcescens, both regulated by the QS inducer acyl homoserine lactone (AHL). Molecular docking analysis validated the strong binding of ebselen to specifc QS proteins (1Joe and PigG) of S. marcescens via hydrogen bonds and aromatic interactions, indicating its potent antibioflm potential [93].…”
Section: Ebselen's Efect On Virulence Factors Of Gram-negativementioning
confidence: 85%
“…In another study akin to the aforementioned one, Shaikh et al [93] demonstrated that ebselen impeded Serratia marcescens bioflm attachment by signifcantly reducing cell surface hydrophobicity. Additionally, it proved efective against preformed bioflms by degrading the eDNA component of the EPS matrix, as assessed through quantifcation of bioflm matrix components and crystal violet assay and validated by scanning electron microscopy analysis.…”
Section: Ebselen's Efect On Virulence Factors Of Gram-negativementioning
confidence: 95%
“…In this experiment untreated bacterial cells serve as negative control. Bacterial growth was measured by spread plate method at every hour, incubated for 24 h and cells were counted and the graph was plotted for time on X-axis and Log 10 CFU ml −1 on Y-axis [55].…”
Section: Time-kill Assay and Colony Forming Unit (Cfu) Assaymentioning
confidence: 99%